Three reasons why food system transformations are contested, and why food system scientists and policymakers should care - Westengen, Ola T.; Lecy, Kate Schneider; Angelsen, Arild; Aspholm, Marina E.; Bjugstad, Nils; Eriksen, Siri H.; Haug, Ruth; Karlsson, Caroline; Olsen, Hanne F.; Rognli, Odd Arne; Schwarm, Angela; Smedshaug, Christian A.; et al. (Frontiers in Sustainable Food Systems, 2025)
Over the last years, consortia of researchers with mandates from high-level international policy forums have published comprehensive assessments and indicator frameworks defining human welfare needs and planetary boundaries for food systems transformations. Despite the evidence presented, scientific assessments and guidelines on food production and diets remain hotly contested. In this Perspective we discuss three reasons why this is so: goal conflicts, disciplinary framing, and power and influence. Understanding and addressing the reasons for discord and polarization are important to build common ground and mobilize the necessary collective action for food system transformations.